Cohort profile: National Diabetes Audit for England and Wales. Issue 9 (14th June 2021) - Holman, Naomi; Knighton, Peter; Wild, Sarah H.; Sattar, Naveed; Dew, Chris; Gregg, Edward W.; Khunti, Kamlesh; Valabhji, Jonathan; Young, Bob
Abstract: The National Diabetes Audit (NDA) collates and analyses data on the quality and variation in clinical care and outcomes for people with diabetes. It also provides opportunities to assess trends, determinants, and outcomes of diabetes to help guide clinical and public health priorities. Cohort: Between 1 January 2003 and 31 March 2020, a total of 5, 280, 885 people diagnosed with diabetes were included in at least one NDA data collection. To this date, median follow‐up was 12 and 8 years for people with type 1 diabetes and type 2 diabetes respectively. Comparisons with the 2019/20 Quality and Outcomes Framework show it included 98% of adults in England and Wales with diagnosed type 1 and type 2 diabetes. Data include demographic characteristics (age, sex, ethnicity, age at diagnosis, deprivation), risk factors (HbA1c, blood pressure, cholesterol, body mass index, smoking status) diabetic and cardiovascular complications and deaths. Secondary analysis: Secondary analyses have included comparisons of HbA1c and blood pressure measurements in cohorts with similar characteristics to the Epidemiology of Diabetes Interventions and Complications study and the UK Prospective Diabetes Study; COVID‐19 related mortality in people with type 1 and type 2 diabetes and incidence of type 2 diabetes following admission to intensive care units. Future plans: Commissioned NDA reports will continue to inform service development in England and Wales. The same data, with or without linkages to other external datasets, are also a rich resource for clinically orientated research.